2019
DOI: 10.1159/000493975
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Topical Cerium Nitrate-Silver Sulfadiazine Application on Overall Outcome in Patients with Calciphylaxis

Abstract: Background: Calciphylaxis (CPX) is a rare and life-threatening disease characterized by vascular calcification and development of painful and necrotizing skin lesions with a challenging management. Mechanisms of CPX are complex and include an imbalance between vascular calcification promoters and inhibitors, and frequently vitamin K deficiency. Objectives: To describe the various presentations and identify predictive factors of death in patients with CPX. Methods: In this multicenter retrospective study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A retrospective study of 71 patients with calciphylaxis undergoing sodium thiosulfate treatment showed that cerium nitrate-silver sulfadiazine therapy might be useful for vascular decalcification and infection prevention. 28 A study evaluating a biofilm of purified collagen matrix with polyhexamethylene biguanide showed complete ulcer healing and re-epithelization in a patient with calciphylaxis. 23 Use of the novel therapy SNF472, an intravenous formulation of myoinositol hexaphosphate, to inhibit hydroxyapatite crystal formation and prevent vascular calcification has shown potential therapeutic benefit.…”
Section: Postoperativementioning
confidence: 99%
“…A retrospective study of 71 patients with calciphylaxis undergoing sodium thiosulfate treatment showed that cerium nitrate-silver sulfadiazine therapy might be useful for vascular decalcification and infection prevention. 28 A study evaluating a biofilm of purified collagen matrix with polyhexamethylene biguanide showed complete ulcer healing and re-epithelization in a patient with calciphylaxis. 23 Use of the novel therapy SNF472, an intravenous formulation of myoinositol hexaphosphate, to inhibit hydroxyapatite crystal formation and prevent vascular calcification has shown potential therapeutic benefit.…”
Section: Postoperativementioning
confidence: 99%
“…Among these, 5 (9.6%) involved clinical studies that examined antioxidants for treatment of VC, while 47 (90.4%) involved experimental studies. For clinical therapeutic studies, four (80%) used parenteral sodium thiosulfate (STS), while one (20%) used topical cerium nitrate 1317 . For experimental approaches, totally 36 compounds with antioxidant property have been tested against VC, including 12 natural dietary substances, 5 natural non-dietary substances, and 19 pharmaceuticals or synthetic chemicals (Fig.…”
Section: Strategy Of Literature Searchmentioning
confidence: 99%
“…We identified five clinical studies testing one parenteral and the other topical agent with an antioxidative ability regarding their efficacy in treating VC (Table 2) 1317 . STS, which has been repeatedly tested in experimental models for inhibiting VC progression, is also used clinically to treat calcification involving arteries from different anatomical locations.…”
Section: Clinically Tested Antioxidants For Treatment Of Vcmentioning
confidence: 99%
See 2 more Smart Citations